Correlación de un Instrumento de Calidad de Vida relacionado con Salud Oral entre niños de 8 a 10 años y sus acudientes en Bogotá - Tellez, Marisol; Martignon, Stefania; Lara, Juan Sebastian; Zuluaga, Jenny; Barrero, Luis; Builes, Lina; Cordoba, Deisy; Gomez, Juliana (CES Odontología, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Arial-BoldItalicMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; @font-face font-family:Arial-ItalicMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:ES-CO; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introducción y Objetivo: Tradicionalmente el estado de salud oral de una población es evaluado mediante indicadores clínicos. Sin embargo, se ha venido reconociendo la importancia del impacto psicosocial de las enfermedades en la calidad de vida poblaciónal. El objetivo de este estudio es describir la calidad de vida relacionada con salud oral en niños de 8-10 años estratificando por género y tipo de institución. Materiales y Métodos: Validación lingüística del cuestionario COHQoL por medio de a)Traducciones reversas b)Prueba piloto c)Análisis de contenido por odontólogospediatras. El cuestionario de 29-items fue distribuido a 168 niños de 8-10 años de edad. Se realizó análisis descriptivo incluyendo tablas de frecuencia y promedios. Se exploraron diferencias estadísticas entre género y tipo de institución mediante la prueba exacta de Fishers (p-value- menor que 0.05). Resultados: Cerca del 50% de los niños percibieron que sus dientes estaban de más o menos a mal, y 42% reportaron sentir dolor en el último mes. 43% reportó sentirse preocupado acerca de lo que los otros piensan de sus dientes. 52% de las niñas experimentaron dolor dental durante el último mes (niños 33%), y además reportan haber faltado al colegio por esta razón (p-value 0.008). Finalmente, en las escuelas públicas se tiende a faltar más (14%) en comparación con las escuelas privadas (6%). Conclusión: La información de calidad de vida relacionada con salud oral es útil para evaluar salud oral en la población considerando el impacto psicosocial de las enfermedades orales en el bienestar general. Abstract <!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Arial-BoldItalicMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; @font-face font-family:Arial-ItalicMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:ES-CO; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Arial-BoldItalicMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; @font-face font-family:Arial-ItalicMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:ES-CO; span.shorttext mso-style-name:short_text; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction and Objective: Traditionally, the oral health status of a population is assessed through clinical indicators. However, in the last recent years, the importance of the psycho social impact of oral diseases on the population’s quality of life has been recognized. The objective of the study is to describe quality of life factors related to oral-health among children 8-10 years-old stratifying by gender and type of institution. Materials and Methods: Linguistic validation of the COHQoL questionnaire was conducted through: a)Forward-backward independent-translations, b)Pilot testing, and c)Reconciliation of this translation by pediatric-dentists. The 29-item-questionnaire was selfadministered in a sample of 168 children 8-10 years old. Tables of frequencies and means were generated. Statistical differences between gender and type of institution were explored using Fishers Exact Test (p-value less than 0.05) Results: Around 50% of the subjects perceived that their teeth were in a more or less to a bad condition, and 42% reported feeling dental pain during the last month. Nearly 43% reported being worried about what others think about their teeth. 52% of females experienced dental pain during the last month compared to males (33%), and missed schooldays due to this cause (p-value 0.008). Finally, those in public schools tended to miss more frequently (14%) schooldays due to dental problems compared to subjects in private schools (6%). Conclusion: Information from an oral health quality of life questionnaire may be useful for assessing population’s oral health considering the psychosocial impact of oral conditions on the general wellbeing.